A produção de períodos de atraso de reforço sem emissões de respostas: efeitos da duração do intervalo, treino no esquema com resetting e sinalização do período - Panetta, Paulo André Barbosa (2013)
The production of delay of reinforcement with abstains of responses in the delay was studied with four rats. Four experiments were conducted, with one rat in each experiment, and a unique procedure for each study. It was planned an increase in one second upon the duration of the delay in Experiment I, after every three consecutive sessions without responding during the delays. In Experiment II, the delay of reinforcement was kept constant at eight seconds. Experiment III was identical to the previous one, except that the delay periods were signaled. The delay was also signaled in Experiment IV, with an increase of one second on it s duration after every three consecutive sessions without responding during the delay periods. It was only in the last experiment that the occurrence of three consecutive sessions without emissions on the delay periods was observed. This happed on Phases I and II, but not in Phase III. In some few sessions of Experiment I, there was no responding during reinforcement delay, but not for three consecutive sessions. In Experiments II and III, there was not a session without responding upon the delays periods. But it was recorded a reduction in the frequency of emissions during the sessions of both of the experiments, especially in Experiment II. The results indicate that, unless there is an explicit training, emissions will be recorded in the delay periods. The results were discussed from the procedures outlined for each experiment, focusing on the signal functions, the length of delay and the different effects between reinforcement delay resetting and non resetting